Competition policy questions in mobile network sharing - Zoltán Pápai; Gergely Csorba; Péter Nagy; Aliz McLean (International Telecommunications Society (ITS), 2018)
Network sharing agreements have become increasingly widespread in mobile telecommunications markets. They carry undeniable advantages to operators and consumers alike, but also the potential for consumer harm. Not all NSAs are created equal: the assessment of the balance of harm and benefits to customers due to an NSA is a complex endeavour. In this paper, we present a framework for the competitive assessment of NSAs, detailing the possible concerns that may arise, the main factors that influence their seriousness, ways to mitigate the concerns and the principles of assessing efficiency benefits.
Keywords: 330; mobile markets; network sharing; competition; competition assessment